Efektivitas Gamified Learning berbasis Mode Gold Quest Blooket terhadap Penguasaan Mufradāt Bahasa Arab - Taufik Nurhuda; Hasan Syaiful Rizal; Miftachul Taubah (JICALLS: Journal of Arabic Education, Linguistics, and Literature Studies, 2026)
Arabic vocabulary mastery remains a persistent challenge in foreign language learning, while empirical evidence regarding the effectiveness of specific gamified learning modes, particularly Blooket Gold Quest, in Madrasah Aliyah contexts remains limited. This study examined whether gamified learning using Blooket Gold Quest was associated with higher Arabic vocabulary mastery than conventional instruction. A quantitative quasi-experimental approach with a pretest-posttest control group design was employed, involving 28 eleventh-grade students at Madrasah Aliyah Sunan Ampel Kejayan, Indonesia, consisting of 14 students in the experimental group and 14 students in the control group. Data were collected using a 20-item multiple-choice vocabulary test and analyzed through a paired-samples t-test, an independent-samples t-test, and Cohen's d effect size. The findings showed that both groups improved after instruction; however, the experimental group achieved higher posttest scores than the control group. The independent samples t-test indicated a statistically significant difference between groups (t = 2.172, p = .039), accompanied by a large practical effect (Cohen's d = 0.821). These findings suggest that integrating the Gold Quest mode into Arabic vocabulary instruction may support higher vocabulary achievement than conventional classroom practice. This study extends empirical evidence regarding the pedagogical potential of the Gold Quest game mode in enhancing Arabic vocabulary learning among Madrasah Aliyah students and provides practical implications for integrating gamified learning into Arabic language instruction.